Pengaruh Pemberian Alkohol Secara Akut Terhadap Memori Pada Tikus (Rattus norvegicus) - Sri Nabawiyati Nurul Makiyah (LP3 UMY, 2015)
The aim ofthis studv is to reveal the effects ofacutely admitted alcohol on memory by measuring the 8 arm radial maze performance of the r(rts. In this study, rats are divided randomly into three groups i.e. control group, treatment conlrol group and lrealment Efoup. Each group contains 5 rats. Rdts were adapted tnto 8 arm radial maze for 10 minutes Jor seven days subsequently without giving a bait except in the sixth day which was given a bail into the tip, the middle and the door of arms and in the seventh day a bait was given into those arms excepl the door of arms.